2000
DOI: 10.1021/bi991281u
|View full text |Cite
|
Sign up to set email alerts
|

Tumor Suppressor INK4:  Quantitative Structure−Function Analyses of p18INK4C as an Inhibitor of Cyclin-Dependent Kinase 4

Abstract: We report the first detailed structure-function analyses of p18 INK4C (p18), which is a homologue of the important tumor suppressor p16 INK4A (p16). Twenty-four mutants were designed rationally. The global conformations of the mutants were characterized by NMR, while the function was assayed by inhibition of cyclin-dependent kinase 4 (CDK4). Most of these mutants have unperturbed global structures, thus the changes in their inhibitory abilities can be attributed to the mutated residues. The important results a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
33
0

Year Published

2003
2003
2012
2012

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 21 publications
(35 citation statements)
references
References 26 publications
2
33
0
Order By: Relevance
“…As revealed in the crystal structure of P16/CDK6 15 (a close homolog of CDK4), and other biochemical studies [16][17][18] (Figure 1), contacts between P16 (or other INK4 proteins, in general) and CDK4 occur in discontinuous patches, and a number of residues located in both loop and helical regions of P16 contribute to CDK4 binding through electrostatic, hydrogen bonding, and van der Waals interactions 3 . While mutations of most of CDK4-interacting P16 residues only lead to mild decrease in its inhibitory activity, the D84H mutant of P16 (a mutant found in human cancers), or the corresponding mutant of P18, D76A, loses all inhibitory activity even though these two mutants are still able to bind to CDK4 16,18 . On the other hand, it has been reported that CDK4 R24C, a mutant frequently found in human cancers, retains its kinase activity but is resistant to P16 inhibition 19,20 .…”
Section: Introductionmentioning
confidence: 82%
“…As revealed in the crystal structure of P16/CDK6 15 (a close homolog of CDK4), and other biochemical studies [16][17][18] (Figure 1), contacts between P16 (or other INK4 proteins, in general) and CDK4 occur in discontinuous patches, and a number of residues located in both loop and helical regions of P16 contribute to CDK4 binding through electrostatic, hydrogen bonding, and van der Waals interactions 3 . While mutations of most of CDK4-interacting P16 residues only lead to mild decrease in its inhibitory activity, the D84H mutant of P16 (a mutant found in human cancers), or the corresponding mutant of P18, D76A, loses all inhibitory activity even though these two mutants are still able to bind to CDK4 16,18 . On the other hand, it has been reported that CDK4 R24C, a mutant frequently found in human cancers, retains its kinase activity but is resistant to P16 inhibition 19,20 .…”
Section: Introductionmentioning
confidence: 82%
“…On one hand, ARs do not recognize specific sequences of targets, unlike SH2 that recognizes sequences with phosphorylated Tyr (70) and SH3 that binds to sequences that are usually proline rich and exhibit a polyproline II helix conformation (71). On the other hand, AR binding involves discontinuous patches of residues dispersed in the whole molecules of both the AR protein and its target (18,57,72), while SH2 or SH3 binding usually involves a localized region of SH2 or SH3 and a very short motif in the target. From this point of view, binding of AR proteins to targets is similar to the association of Fv and Fab fragments with antigens.…”
Section: Specificitymentioning
confidence: 99%
“…Error bars represent standard deviations. their targets (23,27). On the basis of the results of competition experiments, the IκBR67-302 binding site of CDK4 should overlap, at least partially, with the INK4 binding site of CDK4.…”
Section: Resultsmentioning
confidence: 99%
“…GST-tagged and nontagged p16, p18, p18 D76A, and Yar-1 proteins were expressed and purified as described previously (3,23,24).…”
Section: Methodsmentioning
confidence: 99%